Recent HPV self-sampling use for cervical cancer screening in Latin America and Caribbean: a systematic review - Dartibale, Camila B.; Prado, Gabriela de C.; Carobeli, Lucimara R.; Meirelles, Lyvia E. de F.; Damke, Gabrielle M. Z. F.; Damke, Edilson; Morelli, Fabrício; Souza, Raquel P.; , Group PREVENT YOURSELF; da Silva, Vânia R. S.; Consolaro, Marcia E. L.; Sant’Ana, Débora M. G.; et al. (Frontiers in Oncology, 2022)
Objective Cervical cancer is one of the deadliest cancers among women in Latin America and Caribbean (LAC), where most of the countries have not been successful in implementing population-level cytology-based screening programs. An increasing body of evidence supports the validity of self-sampling as an alternative to clinician collection for primary Human papillomavirus (HPV) screening. Therefore, this work aims to summarize recent HPV self-sampling approaches in LAC. Method We performed a systematic review to identify studies focused on “Self-sampling”, and “Human Papillomavirus DNA test” and “Latin America” in PubMed, Embase, Web of Science, Cochrane library and SCOPUS databases for publications dating between 01 January 2017 and 15 March 2022 based on the Preferred Reporting Items for systematic reviews and meta-analysis (PRISMA) statement. Additionally, the references of the articles were carefully reviewed. Results Of the 97 records selected, 20 studies including 163,787 participants, with sample sizes for individual studies ranging from 24 to 147,590 were included in this review. Studies were conducted in 10 LAC countries (18.5%), most with upper medium-income economies (70%). The range of age was 18 to ≥65 years. The vast majority of the studies (85%) addressed the HPV self-sampling strategy for primary cervical cancer screening with overall success for all women including under/never screened and those from special populations (rural, indigenous and gender minorities). Women generally found HPV self-sampling highly acceptable regardless of age, setting of collection, target population or country of residence. Conclusions HPV self-sampling is a promising strategy to overcome the multiple barriers to cervical cancer screening in LAC settings and increasing attendance in underscreened women in countries/territories with well-established screening programs. Furthermore, this strategy is useful even in LAC countries/territories without organized cervical cancer screening and in special populations such as indigenous, rural and transgender women. Therefore, the information generated by the recent initiatives for HPV self-sampling approach in LAC can be beneficial for decision-making in both new and existing programs in the region.